2004
DOI: 10.1007/s00431-004-1572-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasma aldosterone levels in the 1st week of life in infants of less than 30 weeks gestation

Abstract: Plasma aldosterone levels in this extremely premature cohort were significantly greater than those reported in more mature infants. Important determinants were severity of illness and sodium homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 22 publications
3
19
1
Order By: Relevance
“…As one of the direct applications of this study, we propose that urinary aldosterone measurement is the best index for accurate evaluation of the mineralocorticoid effector mechanisms. Plasma aldosterone does not constitute a good parameter at birth in accordance with previous studies, which already reported the lack of correlation between kalemia and plasma aldosterone concentrations (37,38). Instead, the highly significant negative relationship found between urinary aldosterone and plasma potassium concentrations establishes that aldosterone participates to the control of potassium balance.…”
Section: Discussionsupporting
confidence: 83%
“…As one of the direct applications of this study, we propose that urinary aldosterone measurement is the best index for accurate evaluation of the mineralocorticoid effector mechanisms. Plasma aldosterone does not constitute a good parameter at birth in accordance with previous studies, which already reported the lack of correlation between kalemia and plasma aldosterone concentrations (37,38). Instead, the highly significant negative relationship found between urinary aldosterone and plasma potassium concentrations establishes that aldosterone participates to the control of potassium balance.…”
Section: Discussionsupporting
confidence: 83%
“…18 We found a negative correlation between plasma sodium and UAE already during the first three days of life that may confirm the physiological partial aldosterone resistance in human neonates, due to a progressive increase of renal mineralocorticoid receptor expression level in the first days after birth, concurrently with renal maturation. 23,24 In the exploratory analysis we found a significant positive correlation between UAE and gestational age and birth …”
Section: Discussionsupporting
confidence: 75%
“…3,4,10 While clear reference values for aldosterone exist for paediatric populations, few and heterogeneous data are available for term and preterm neonates. [11][12][13][14][15][16][17][18] The studies carried out during the neonatal period varied in the timing of sampling and almost all determined aldosterone plasma level.…”
Section: Discussionmentioning
confidence: 99%
“…These conditions appear to result from an impaired capacity to regulate water and sodium homeostasis, mimicking partial aldosterone resistance (Martinerie et al, 2009a). Previous studies proposed that the reduced kidney responsiveness to aldosterone could be related to low mineralocorticoid receptor (MR) expression during human development, as demonstrated by the lack of detectable MR immunoreactivity in the renal cortical collecting duct during the late gestational age and neonatal periods, contrasting to the high aldosterone levels (Bourchier, 2004;Martinerie et al, 2009b). Our results indicate that neonate salt wasting syndrome could also be the consequence of a primary defect in aldosterone secretion in preterm infants, as suggested by low level of adrenal CYP11B2 expression before 28 WG.…”
Section: Discussionmentioning
confidence: 94%